Analyzing and Enhancing Data Management for the E-Library Transaction System - Marlindawati, .; Misinem, .; Padji, Adhiatma (INTI International University, 2024)
This study examines the role of information systems in enhancing data management and operational efficiency within library operations, focusing on the case of SMP Negeri 8 Palembang. Information systems are designed to facilitate the management and storage of data, enabling the generation of precise and accurate information. Such systems can minimize errors and improve efficiency and speed in data-related operations, such as borrowing and returning books.The research analyzes the limitations of manual processes currently in place and evaluates the potential benefits of a web-based information system for library book transactions. Using PHP for development and MySQL for database management, the study investigates how such a system can address inefficiencies and error-prone manual processes.Key findings from this research indicate that the implementation of a web-based application significantly enhances the ability of library staff to record and process borrowing and returning transactions, as well as manage student membership data. This analysis underscores the transformative impact of technology in reducing operational bottlenecks and fostering a more efficient, accurate, and user-friendly library management environment at SMP Negeri 8 Palembang. The study not only highlights system development outcomes but also provides insights into the broader implications of integrating technology into library operations